Mutagenesis and expression of methane monooxygenase to alter regioselectivity with aromatic substrates. Issue 13 (30th June 2017) - Lock, Malcolm; Nichol, Tim; Murrell, J. Colin; Smith, Thomas J.
Abstract: Soluble methane monooxygenase (sMMO) from methane-oxidising bacteria can oxygenate more than 100 hydrocarbons and is one of the most catalytically versatile biological oxidation catalysts. Expression of recombinant sMMO has to date not been achieved in Escherichia coli and so an alternative expression system must be used to manipulate it genetically. Here we report substantial improvements to the previously described system for mutagenesis of sMMO and expression of recombinant enzymes in a methanotroph ( Methylosinus trichosporium OB3b) expression system. This system has been utilised to make a number of new mutants and to engineer sMMO to increase its catalytic precision with a specific substrate whilst increasing activity by up to 6-fold. These results are the first 'proof-of-principle' experiments illustrating the feasibility of developing sMMO-derived catalysts for diverse applications. Abstract : Regioselectivity of soluble methane monooxygenase towards an aromatic substrate was increased via site-directed mutagenesis, indicating that this broad substrate-range enzyme can be engineered into a precise biocatalyst.